E-124 Combined diluted n-BCA glue and particle embolization followed by a 'Sugar Rush' D5W Bolus in middle meningeal artery (MMA) embolization for chronic subdural hematomas: a prospective safety and technical feasibility study. (4th August 2020) - Kaur, G; Dakay, K; Cooper, J; Bowers, C; Santarelli, J; Gandhi, C; Al-Mufti, F
Abstract : Introduction: In recent years, embolization of the middle meningeal artery (MMA) for treatment of refractory or recurrent chronic subdural hematomas (SDH) has gained momentum. The rationale is the formation of the neo-membrane, with the MMA providing feeding vessels to the outer membrane connected to the dura mater. Various techniques like the use of polyvinyl particles and Onyx have been explored. We present the technical feasibility of using very diluted n-butyl-2-cyanoacrylate (NBCA) for embolization. Methodology: Patients were enrolled from Westchester Medical Center from September 2019- March 2020, with chronic refractory or recurrent subdural hematomas. Informed consent was obtained from patients and/or families. Embolization of the frontal and parietal branches of the MMA was performed using a very dilute mixture of 1:6 n-BCA and ethiodized oil, with 5% dextrose (D5) boluses from the guide catheter to improve the distal penetration of the glue. Visibility was improved by using Tantalum powder. Cases with ophthalmic collaterals from the MMA were excluded. The prowler select plus Codman Neuro (Johnson & Johnson), 2.3. 0.021 was used for all cases. Follow up CT head was performed at day 7, day 21 and 3 months. Results: A total of 11 patients were prospectively enrolled. The mean age was 71 years, male to female ratio of 2:1. 10 of the 11 cases were traumatic, one was a patient with lupus on anticoagulation. A total of 5 of 11 patients were on anticoagulation at the time of the SDH. Nine of the 11 patients had prior neurosurgical intervention including subgaleal drains and burr holes. The 7 day follow-up CT head was available for 9 of 11 and demonstrated improvement (>50% reduction in SDH volume) in 7/9 (77%), with 2/9 (22%) showing an unchanged or stable SDH. Day 21 CT head was available for 5/7 patients (71%), all demonstrating significant further improvement (>75% reduction in SDH volume). There were no intra or post procedural complications (non-target embolization or unintentional retention of the catheter) in the 11 patients enrolled (0%). Conclusion: Embolization of the MMA using very diluted n-BCA and ethiodized oil (1:6) is safe and effective for chronic SDH patients with a low risk of recurrence, and is considered an effective therapeutic intervention to arrest hematoma enlargement and promote resolution. The use of a 'sugar rush' D5 bolus improves distal penetration of the glue. Disclosures: G. Kaur: None. K. Dakay: None. J. Cooper: None. C. Bowers: None. J. Santarelli: None. C. Gandhi: None. F. Al-Mufti: None.